PERUBAHAN TEMPORAL HUTAN MANGROVE DAN PENGARUHNYA TERHADAP PENYIMPANAN GAS KARBON BIRU (STUDI KASUS KEPULAUAN KANGEAN, SUMENEP, JAWA TIMUR) - Ruth Rosalinda, Giok
Mangrove forest loss occurs 3 to 5 times faster than forest loss in general. In the 2000-2014 period, Indonesia was recorded as the largest contributor to the loss of mangrove forests in the world, namely 4,364 km2 or approximately 311 km2 per year, even though mangroves as carbon storage are so important in mitigating global climate change. To perform spatial analysis, the rate of mangrove decline can be determined by comparing mangrove land cover data from year to year with remote sensing support. The purpose of this study is to estimate above-ground carbon stocks based on degraded mangrove areas, and to analyze the effect of mangrove degradation on above-surface carbon storage in the Kangean Islands from 2007 to 2016. The purpose of this study is to estimate carbon stocks using NDVI calculations, SAVI and height models. The data used are primary data in the form of Landsat 7 and Landsat 8 images with a spatial resolution of 30 meters and height image data of the Global Canopy Height with a spatial resolution of 30 meters. The results obtained in this research are that there is an average carbon stock with a range of 10-15 tonnes / ha for the NDVI method, 15-18 tonnes / ha for the SAVI method, and 12-12.4 tonnes / ha for the high method. Meanwhile, the correlation results show that the mangrove area has the highest correlation with the carbon stock resulted from the SAVI method, but with the inversely proportional conditions, the area has a substantial correlation with the carbon stock resulted from the NDVI method, and finally the correlation between mangrove area and carbon stock resulted from the high method is negligible.